Review of the use of prophylactic drain tubes post‐robotic radical prostatectomy: Dogma or decent practice?. Issue 4 (9th June 2020) - Nzenza, Tatenda C.; Ngweso, Simeon; Eapen, Renu; Rajarubendra, Nieroshan; Bolton, Damien; Murphy, Declan; Lawrentschuk, Nathan
Abstract: Objective: To assess the necessity of routine prophylactic drain tube use following robot‐assisted radical prostatectomy (RARP). Method: We performed a literature review using the Medline, Scopus, and Web of Science databases with no restriction of language from January 1900 to January 2020. The following terms we used in the literature search: prostatectomy, radical prostatectomy, robot assisted, drainage, and drain tube. Results: We identified six studies that examined the use of routine prophylactic drain tubes following RARP. One of these studies was a randomized study that included 189 patients, with 97 in the pelvic drain (PD) arm and 92 in the no pelvic drain (ND) arm. This non‐inferiority showed an early (90‐day) complication rate of 17.4% in the ND arm versus 26.8% in the PD arm ( P  < .001). Another non‐inferiority randomized control trial (RCT) showed a complication rate of 28.9% in the PD group versus 20.4% in the ND group ( P  = .254). Similarly, the other studies found no benefit of routine use of prophylactic drain tube after RARP. Conclusion: Drain tubes play a role during robotic‐assisted radical prostatectomy, however, following a review of the current available literature, they can be safely omitted and we suggest that clinicians may be selective in their use.